A wideband circularly polarized dielectric resonator antenna excited with conformal‐strip and inverted L‐shaped microstrip‐feed‐line for WLAN/WI‐MAX applications. Issue 10 (27th July 2016) - Kumar, Rajkishor; Kumar Chaudhary, Raghvendra
ABSTRACT: A new wideband circularly polarized dielectric resonator antenna (DRA) has been developed and presented in this article. The proposed antenna consisting rectangular and cubical‐shaped dielectric resonator (DR) with optimum gap excited by using combination of conformal‐strip and inverted L‐shaped microstrip‐feed‐line. The combinations of two different feeds (i.e., conformal‐strip and microstrip‐fed‐line) excite orthogonal modes in two DRs to generate circular polarization. The gap between these DRs and conformal strip offers wideband of impedance and axial ratio bandwidth. Designed antenna offers measured −10 dB impedance bandwidth of 27.36% (at center frequency 5.78 GHz) and measured 3‐dB axial ratio bandwidth has been achieved in broadside direction of 23.00% (at center frequency 5.65 GHz). It has been confirmed from the radiation pattern that the antenna having right hand circular polarization (RHCP). Proposed antenna can be used for wireless communication systems such as WLAN/Wi‐MAX applications. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2525–2531, 2016